2011
DOI: 10.2139/ssrn.1980674
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Labor Market Return, Parental Leave Policies, and Gender Inequality in Housework

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
(31 reference statements)
1
5
1
Order By: Relevance
“…Furthermore, the 2007 reform appears to have increased fathers' child care time in West-Germany even after controlling for their own take-up of leave, their paid work hours and for indirect effects through changes in their partners' timing and extent of labor market return. These results are in line with the broad associations with family friendly policies found by previous studies on child care time based on repeated cross-sections of several countries (Craig and Mullan 2010;2011;Hook 2006).…”
Section: Unobserved Heterogeneity and Control Variablessupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, the 2007 reform appears to have increased fathers' child care time in West-Germany even after controlling for their own take-up of leave, their paid work hours and for indirect effects through changes in their partners' timing and extent of labor market return. These results are in line with the broad associations with family friendly policies found by previous studies on child care time based on repeated cross-sections of several countries (Craig and Mullan 2010;2011;Hook 2006).…”
Section: Unobserved Heterogeneity and Control Variablessupporting
confidence: 91%
“…The finding of direct associations of parental leave policies with child care in couples provides an interesting contrast with a recent study on housework, which found no evidence of direct parental leave policy associations with housework time in British and German couples with young children (Schober 2011). This suggests that parental leave policies are more likely to influence conceptions of motherhood and fatherhood than gender ideologies relating to the division of unpaid work in general.…”
Section: Unobserved Heterogeneity and Control Variablescontrasting
confidence: 77%
See 1 more Smart Citation
“…For example, Pettit and Hook () found that parental leaves of up to 2 years are associated with an increased probability of employment for mothers of young children, but after 2 years, leaves have a negative effect on the likelihood of employment. Schober () found that extensions beyond 1 year are associated with delays in the labor market return of mothers.…”
Section: Maternity Leavementioning
confidence: 99%
“…Other research also has found that living in a country with longer parental leave is associated with a less egalitarian division of housework (Geist & Cohen, ; Hook, ). In an effort to better understand the pathway through which maternity leave affects the division of housework in the family, Schober () analyzed a longitudinal data set of German and British parents and found that parental leave, of even a short to moderate duration, leads to a more traditional division of labor by slowing mothers' labor market return after childbirth. Mothers' rapid return to full‐time work after childbirth reduced the trend toward a more traditional division of labor.…”
Section: Maternity Leavementioning
confidence: 99%